INDIVIDUAL PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS IN TEACHING FOREIGN LANGUAGE SCIENCES - Jabbarov, Ulugbek (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT INDIVIDUAL PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS IN TEACHING FOREIGN LANGUAGE SCIENCES